2009
DOI: 10.1074/jbc.m109.030601
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome-dependent Processing of Topoisomerase I-DNA Adducts into DNA Double Strand Breaks at Arrested Replication Forks

Abstract: Reversible topoisomerase I (Top1)-DNA cleavage complexes are the key DNA lesion induced by anticancer camptothecins (CPTs) (e.g. topotecan and irinotecan) as well as structurally perturbed DNAs (e.g. oxidatively damaged, UV-irradiated, or alkylated DNA). It has been proposed that Top1 cleavage complexes arrest advancing replication forks, triggering the formation of DNA double strand breaks (DSBs) because of replication fork runoff at the Top1 cleavage complex sites on the leading strand. In this study, we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
66
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 43 publications
7
66
1
Order By: Relevance
“…Next, we investigated the involvement of TIP and RIP pathways in the activation of CPT-induced DDR and found that RPA phosphorylation was mainly initiated through the RIP pathway of TOP1cc, as previously reported [21]. The involvement of RIP pathway in the activation of CPT-induced DDR is supported by a recent study showing the role of TOP1cc-mediated and replication-dependent DNA DSBs in the CPT-induced γ-H2AX activation [12]. Nevertheless, several DDR activations, including γ-H2AX, ATM and Chk2 phosphorylation, have also been observed in nonreplicating, post-mitotic cells treated with CPT [11], suggesting a replication-independent mechanism for the activation of CPT-induced DDR.…”
Section: Introductionsupporting
confidence: 56%
See 4 more Smart Citations
“…Next, we investigated the involvement of TIP and RIP pathways in the activation of CPT-induced DDR and found that RPA phosphorylation was mainly initiated through the RIP pathway of TOP1cc, as previously reported [21]. The involvement of RIP pathway in the activation of CPT-induced DDR is supported by a recent study showing the role of TOP1cc-mediated and replication-dependent DNA DSBs in the CPT-induced γ-H2AX activation [12]. Nevertheless, several DDR activations, including γ-H2AX, ATM and Chk2 phosphorylation, have also been observed in nonreplicating, post-mitotic cells treated with CPT [11], suggesting a replication-independent mechanism for the activation of CPT-induced DDR.…”
Section: Introductionsupporting
confidence: 56%
“…CPT treatment has been shown to induce the formation of TOP1cc and subsequent activation of signaling molecules and corresponding DDR [11][12][13]. We first used the alkaline comet assay to detect DNA SSBs induced by CPT treatment and to characterize the reversibility of these breaks.…”
Section: Cellular Exposure To Cpt Results In Generation Of Top1-linkementioning
confidence: 99%
See 3 more Smart Citations